URGENSI PEMBUATAN UNDANG-UNDANG CONTEMPT OF COURT UNTUK MENEGAKKAN MARTABAT DAN WIBAWA PERADILAN - HP Panggabean (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
It’s time to draft the contempt of court bill to guarantee the dignity and soverignity of court institution and the law enforcement process, the supreme of court makes strong effort to improve the supervision of judge performance quality and administrative official judiciaryKeywords : Act Urgency, Contempt of Court, Court Dignity